Testicular inguinal ectopia following hernia repair in children - D. S. Zolotukhin; O. S. Pavlova; I. A. Filatov (Вестник урологии, 2024)
Introduction. Inguinal ectopic testis is a rare complication after inguinal hernia repair. In modern literature, there are few articles devoted to this problem.Objective. To study the testicular elevation mechanisms after inguinal hernia surgery in children and methods to treat this complication.Materials & methods. A cross-sectional retrospective analysis of medical records of male children who underwent inguinal plasty between January 2018 and December 2023 was performed at the Chelyabinsk Regional Children's Clinical Hospital. Those who underwent subsequent orchopexy for ipsilateral cryptorchidism were identified. Cryptorchidisms that were misdiagnosed were excluded.Results. A total of 1140 boys with inguinal hernias were treated, of which 978 (86%) were operated on laparoscopically using the PIRS technique, and 162 (14%) underwent open hernia repair. In nine (0.7%) children, an ectopic testicle in the groin was detected after surgery. During orchiopexy, extensive adhesions and scars in the inguinal canal were found only in two cases after open plastic surgery. The processus vaginalis remained intact after laparoscopic repair and partially after open hernia repair.Conclusion. Ectopic testicles in patients undergoing inguinal hernia repair can be successfully treated with orchiopexy performed through the inguinal approach.